Urological complications after Kidney transplantation - Chalise, P R; Sharma, U T; Gyawali, P R; Shrestha, G N; Joshi, B R; Gurung, G S; Ghimire, R K; Kafle, M P; Sigdel, M R; Shah, D S; Raut, K B; Sidharth, Mr. (Kathmandu University Medical Journal, 2012)
Background Renal transplantation is a regular service at Tribhuvan University Teaching Hospital and complications have been known to occur after it. This study was conducted to assess complications after transplantation. Objectives To determine the incidence of urological complications after living related renal transplantation at Tribhuvan University Teaching Hospital. Methods A clinical study was performed (from August 2008 to July 2010) which included 50 living-related renal transplantations at Tribhuvan University Teaching Hospital. All the donors and recipients were evaluated preoperatively with necessary investigations and followed up postoperatively with standard hospital transplant protocol. The incidence of urological complications were documented and analyzed. Results Fifty living-related, renal transplantations were carried out during the study period. Seven doors had minor post operative complications; three had post operative fever, two had chest infections and each one had superficial surgical site infections and severe pain at incision site. Ureteroneocystostomy was performed with double J stent in all recipients. Urological complications were noted in 12 (24%) recipients. Clinical significant hematuria occurred in four cases. One patient had ureteric necrosis and urinary leak which required re-exploration post operatively. Two patients developed delayed ureteric stricture which were managed by antegrade Double J stenting and ureteric reimplantation. Peri-graft abscess occurred in two cases, which were drained percutaneously. surgical site infections was seen in one case. Conclusions Urological complications are inevitable in renal transplantation and our complications rate appears similar to that reported in literature. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6216 Kathmandu Univ Med J 2010;8(3):299-304